N.C. Const. of 1875, art. I, § 24 - (:unkn) unknown (My University, 1875)
Reiterated the terms of the US second amendment. Included a second portion declaring that standing armies are dangerous to liberty and ought not to be kept up. A third section declared that nothing herein contained shall justify carrying concealed weapons or prevent the legislature from enacting penal statutes against said practice.
Keywords: GUARANTEED RIGHT